Potential Carbon Content of Seagrass Species Diversity in Coastal Waters of Central Lombok - Eva Rosdiana Sari; Abdul Syukur; Moh. Liwa Ilhamdi (Jurnal Biologi Tropis, 2021)
The marine environment has a significant role in maintaining the balance of gas exchange in the air, especially between oxygen and carbon dioxide. The potential of the marine environment for gas exchange is supported by the existence of marine ecosystems such as seagrass ecosystems. This is in accordance with the blue carbon concept which plays a role in environmental mitigation in reducing carbon through the coastal environment. Therefore, the purpose of this study was to assess the potential carbon content of the diversity of seagrass species at three locations of seagrass beds in the coastal waters of Central Lombok. The research method uses the line transect method and the ashing method. Seagrass vegetation data were analyzed using community structure analysis (diversity, uniformity and dominance). In addition, analysis of seagrass biomass and carbon content of seagrass was carried out. Furthermore, the regression analysis between seagrass density as the independent variable (X) and the carbon content of seagrass species as the dependent variable (Y). The results of the study found 8 species of seagrass found in the waters of Central Lombok with moderate diversity ranging from 1.59-1.77. The value of seagrass biomass in the waters of Central Lombok is dominated by the bottom substrate with a value of 3.38ÃÂ±1.58 gbk.m-2 while the upper substrate with a value of 1.69ÃÂ±0.98 gbk.m-2. The carbon value of seagrass in Central Lombok waters is dominated by the bottom of the substrate with a value of 1.39ÃÂ±0.22 tonC/Ha while the upper substrate is 0.72ÃÂ±0.13 tonC/Ha. Meanwhile, the results of the calculation of the Pearson's correlation (r) between the density of each type of seagrass as an independent variable (X) and the carbon content of each type of seagrass as the dependent variable (Y) shows the equation y = 10,608x + 70,155 with a correlation coefficient of 0.64 which belongs to the category medium and the coefficient of determination (r2) is 0.41. The conclusion of this study is that there is no significant relationship between the density of each type of seagrass and the carbon of each type of seagrass as indicated by the value of Fcount (4.17) < Ftable (6.60) with a value of =0.05 so that H0 is accepted and Ha is rejected.